Catalytic performances of Ni-based catalysts on supercritical water gasification of phenol solution and coal-gasification wastewater. (5th February 2019) - Wang, Yuzhen; Zhu, Yitong; Liu, Zhuan; Wang, Laibin; Xu, Donghai; Fang, Changqing; Wang, Shuzhong
Abstract: Activity and stability of the supported Ni-based catalysts for the gasification performances of phenol solution and coal-gasification wastewater in supercritical water were studied in a continuous reactor at 480 °C, 25 MPa and oxygen ratio of 0.2 for 50 h operation. The influences of the supports (γ-Al2 O3, active carbon (AC) and carbon nanotube (CNT)) on gas yields, gasification efficiencies for phenol solution were investigated, and the loading amount of Ni were optimized. Results showed that the catalytic activity and the stability of the catalysts followed the order of Ni/CNT > Ni/AC > Ni/γ-Al2 O3 . The activity of Ni/AC and Ni/γ-Al2 O3 decreased after 30 h continuous operation, and there occurred significant leaching of Ni 2+ . For Ni/CNT catalyst, H2 yield increased obviously when the loading amount of Ni lower than 15 wt%, while increased little at higher loading amount. Then, 15 wt% Ni/CNT with a thickness of 1.5 mm was coated on 316 L stainless steel (SS316L, an economic material usually used as the reactor material), which can act as a "catalytic tube wall" in reactor. The catalytic activity and corrosion resistance of Ni/CNT/SS316L for the gasification of real coal-gasification wastewater were studied. Results showed that Ni/CNT/SS316L gave a great positive effect on H2 production. H2 yield increased from 25.36 mmol/g (total organic carbon) without catalyst to 75.12 mmol/g (total organic carbon) with Ni/CNT/SS316L after operated for 20 h, respectively. However, obvious pealing of the coating was found after 50 h operation. Further study is necessary for the improvement of the coating preparation method. Highlights: Catalytic gasification of phenol was performed at 480 °C, 25 MPa for 50 h operation. Activity and stability of the catalysts were in the order of Ni/CNT > Ni/AC > Ni/γ-Al2 O3 . For Ni/CNT catalyst, best activity was gained at the Ni loading of 15 wt%. Ni/CNT was plated on the surface of 316 L stainless steel to act as a catalyst. Catalytic activity and stability of Ni/CNT/316 L stainless steel were studied.